Production of yellow passion fruit seedlings under irrigation water salinity (Research, Society and Development, 2021)
The use of water with a high salt content is a serious problem in the formation of seedlings and establishment of passion fruit in different areas of the northeast region, which is considered quite expressive in the production of yellow passion fruit. Therefore, the aim of this study was to evaluate the production of yellow passion fruit seedlings in response to the salinity of irrigation water. The experiment was carried out in a greenhouse. Five treatments were studied, consisting of five levels of electrical conductivity of the irrigation water (0.8; 1.6; 2.4; 3.2 and 4.0 dS m-1), distributed in a randomized block design, with 12 replications, and one plant per plot, totaling 60 experimental units. The effects of the treatments were obtained by analyzing the growth, gas exchange and fluorescence of chlorophyll a. Irrigation with water with electrical conductivity above 0.8 dS m-1 negatively affected the growth of passion fruit cv. Round Yellow at 40 days after sowing. Irrigation with 4.0 dS m-1 water compromised gas exchange and chlorophyll a fluorescence, in addition to reducing the electron transport rate of passion fruit seedlings.